Retrospective Evaluation of Disability Reports In Çukurova University Forensic Medicine Department - Hilal, Ahmet; Akgündüz, Eren; Kaya, Kenan; Yılmaz, Kemal; Çekin, Necmi (The Bulletin of Legal Medicine, 2017)
Objective: Disability; is defined as disablement. Disability, a word in Arabic origin, is derived from the word “malady” which means disablement, illness, unstable condition. The loss of function, due to injuries or occupational reasons, which does not improve and continue in a sequential manner despite all the treatments applied is defined as disability and the disability rate—profit loss rate in profession—is determined as the rate determined by using prepared scales—determining the loss amount of the whole body compared to the earning power in the profession. In this study, it was aimed that, revealing the contents of and results of disability reports and discussing results in the light of literature. Materials and Methods: Disability reports sent by courts to Çukurova University Forensic Medicine Department between the dates of 01.01.2013 and 30.06.2016, whom claimed maimed after traffic accidents and other causes like work accidents, examined retrospectively. Results: In total, 3835 disability files submitted by courts were included in the study. There were 2892 male (75.4%) and 943 (24.6%) female cases. The age range was between 1–79 years and it was observed that most of the cases were in the 30-39 age group. 3768 (98.3%) of the cases were injured due to traffic accidents and 67 (1.7%) were injured due to incidents rather than traffic accidents. The average rate of disability was 17.7%. The highest disability rate range was found to be in the 10-19.9 percent group. Of the cases, 587 (15.3%) were found not to have a reduction in earning power in the profession. During the calculation of the disability reports, 833 (21.7%) cases were found to be appraised because there was no item meeting the restriction. Conclusion: It is believed that forensic medicine specialists often fail to provide a standard practice in disability reports. In order to achieve this standardization, it is necessary to increase the number of collaborations. In terms of helping to ensure justice, we think that each of the regulations used in the disability calculation alone is inadequate for which reason it is necessary to establish a new regulation which includes more detailed, current professions.